Socialization of the Importance of Recognizing and Avoiding Negative Content in the Digital World at SMPN 14 Mataram - Toriq Aziz; Vira Estyanty; Baiq Nurhayati; Nidya Yulistira Widyari; Sony Januarda; Baiq Mentari Aprianti; Angga Mulyadin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to recognize and avoid negative content in the digital world applied at SMPN 14 Mataram. This research uses descriptive qualitative method, with data collection through interviews, observation, and documentation. The research subjects were teachers and students at SMPN 14 Mataram. The results showed that there are still many teachers and students exposed to negative content such as: (1) Hoax, (2) Cyberbullying, (3) Pornography, and (4) Hate speech. For this reason, we hope that this activity will increase students' awareness of internet ethics and the importance of choosing positive content.